PENGARUH RELIGIUSITAS TERHADAP ETIKA KONSUMEN PADA GENERASI MILENIAL - Ali Wardhana (CAPITAL: Jurnal Ekonomi dan Manajemen, 2019)
Ethics plays an important role in human life, including in the millennial generation. Ethical assessment in the millennial generation needs attention from producers, considering this generation is a potential market. Thus the purpose of this study is to see the effect of religiosity on consumer ethics in the millennial generation. This study will use primary data and the questionnaireinstrument. The results showed that intrinsic religiosity had a negative effect on ethical judgment while extrinsic religiosity had a positive influence on ethical judgment.Keywords: religiosity, generation milenial, ethic judgement